Aflatoxin B1 contamination of dairy feeds after storage in farm practice in tropical environment - Wantanwa Mongkon (2018)
The objective of this study was to determine the contamination of aflatoxin B1( AF-B1) when keeping various dairy feeds in a farm environment. The study was carried out from March to May 2011 and involved 63 small holder dairy farms belonging to a single dairy cooperative in Chiang Mai province, Thailand. All feed samples used for milking cows including 4 commercial concentrates (CC1 to CC4), by-products from local corn processing factories fermented in plastic bags (SIL), and corn and cob meal or corn dust (CCD). Feed samples were collected 2 times at before and after storage. Farmers were requested to store CC1 to CC4 and CCD for a month and SIL for a week using their routine on-farm storage arrangements. All samples were measured for their AF-B1 concentrations by ELISA. Results showed that AF-B1 concentrations of CC1 to CC4, SIL and CCD before storage were 5.1, 4.1, 4.0, 4.2, 5.5 and 5.5 μg/kg, respectively, and after storage the concentration of AF-B1 were 9.7, 6.5, 9.8, 12.3, 11.4 and 20.0 μg/kg, respectively. CCD at after storage was the only feed that had mean level more than 20 μg/kg. Concentrations of AF-B1 at before storage in all feeds were significantly lower than after storage (P < 0.01), and the increased ratio of AF-B1 levels was approximately 2 to 3 times. The study concluded that increased AF-B1 levels are related to feed types and farm conditions.